Agricultural fertilisers contribute substantially to microplastic concentrations in UK soils - Samuel J. Cusworth; William J. Davies; Martin R. McAinsh; Andrew S. Gregory; Jonathan Storkey; Carly J. Stevens (Communications Earth & Environment, 2024)
Abstract Since their invention, plastics have driven a revolution in behavior in all aspects of our lives, including agriculture. In-use and as a waste material, plastics degrade and accumulate in agricultural systems. Accumulation of plastic pollution in agricultural systems has negative impacts on human health and agricultural productivity but little is known about concentrations of microplastics in soils. Here we used a historical time series to examine changes to microplastic concentrations in agricultural soils over time. Microplastics were stained with Nile Red and quantified using fluorescence microscopy. We demonstrate that microplastic concentrations increased at higher rates in soils that are amended with either organic or inorganic fertiliser between 1966 and 2022, suggesting that agricultural fertilisers are an important contributor to microplastic concentrations in agricultural soils over time. This study provides evidence that agricultural soils are receptors and reservoirs of microplastic pollution, a legacy which is growing over time.